Question about Bagatrix Algebra Solved! 2005 (105101) for PC

4x+8y=20

-4x+2y=-30

Linear Equation:
yearly profits:
In news reports, profits of a compagny this year (T) are often compared with those of last year (L), but actual values of T and L are not always given. this year , a company had profits of $25 million more than last year. the profits were up 30%. determine T and L from these data.
2nd Question: INVESTMENTS

A total of $35,000 was invested at three interest rate: 7,8, and 9%. The interest for the first year was $2830, which was not reinvdeste. The second year the amount originally invested at 9% earned 10% instead, and the other rates remained the same. The total interest the second year was $2960. How much was invested at each rate?

HELP please please

Posted on Oct 19, 2010

X=7

y=-1

Posted on Feb 17, 2009

4x+8y=20

-4x+2y=-30

Posted on Mar 10, 2009

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

goodluck!

Posted on Jan 02, 2017

This is best written as two separate equations:

8x+3y = -23 and 34x+ 5y = -23

Solving the first one for x:

8x = -23-3y

x = -23/8 - 3/8y

Substituting this value for x into the second equation:

34(-23/8 - 3/8y) + 5y = -23

-97.75 - (34)(.375)y + 5y = -23

-97.75 - 12.75y + 5y = -23

-97.75 -7.75y = -23

-7.75y = 97.75-23=74.75

**y **= -74.75/7.75 =** -9.645161**

Substitution back into the equation for x:

x = -23/8 - 3/8(-9.645161)

x = -2.875 + 3.616935

**x** **=.741935**

8x+3y = -23 and 34x+ 5y = -23

Solving the first one for x:

8x = -23-3y

x = -23/8 - 3/8y

Substituting this value for x into the second equation:

34(-23/8 - 3/8y) + 5y = -23

-97.75 - (34)(.375)y + 5y = -23

-97.75 - 12.75y + 5y = -23

-97.75 -7.75y = -23

-7.75y = 97.75-23=74.75

Substitution back into the equation for x:

x = -23/8 - 3/8(-9.645161)

x = -2.875 + 3.616935

Dec 12, 2014 | Bagatrix Algebra Solved! 2005 (105101) for...

First step is to find inequality in the form y<f(x), in this case **y<5-0.5x**. Then graphing it. See captured image

Feb 18, 2011 | Texas Instruments TI-84 Plus Silver...

Given "2R-3S=-10", then "6R-9S=-30".

Given "3R 2S=37", then "6R 4S=74".

Subtract the two equations: "6R-6R 4S --9S = 74 --30",

which reduces to: "4S --9S=104".

Note that 'R' has been eliminated from the equation, as requested.

Solving for 'S' is left as an exercise for the reader.

Given "3R 2S=37", then "6R 4S=74".

Subtract the two equations: "6R-6R 4S --9S = 74 --30",

which reduces to: "4S --9S=104".

Note that 'R' has been eliminated from the equation, as requested.

Solving for 'S' is left as an exercise for the reader.

Sep 03, 2010 | MathRescue Word Problems Of Algebra Lite

4x+7=11 Solve for "x".

subtract 7 from each side of the equation

4x +7(-7)=11(-7) = 4x=4

divide both sides of the equation by 4

4x/4=4/4

therefore

x=1

Correct?

subtract 7 from each side of the equation

4x +7(-7)=11(-7) = 4x=4

divide both sides of the equation by 4

4x/4=4/4

therefore

x=1

Correct?

Dec 06, 2009 | 2006 Harley Davidson FXDI35 35th...

6x+6=4x+12

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Sep 10, 2009 | Audio Players & Recorders

4x+8y=20 || /4

x+2y=5

x=5-2y

-4x+2y=-30 || /2

-2x+y=-15

-2(5-2y)+y=-15

-10+4y+y=-15

5y=-5

y=-1

x=5-2y || y=-1

x=5-2(-1)

x=5+2

x=7

x+2y=5

x=5-2y

-4x+2y=-30 || /2

-2x+y=-15

-2(5-2y)+y=-15

-10+4y+y=-15

5y=-5

y=-1

x=5-2y || y=-1

x=5-2(-1)

x=5+2

x=7

Mar 10, 2009 | Bagatrix Algebra Solved! 2005 (105101) for...

use the simultaneous equation solver software available on ur ti-89 and enter the equation in the form of augmented matrix and you will get ur answer.

Dec 03, 2008 | Texas Instruments TI-89 Calculator

Hi joanmae jmeh;

You can add these equations just like you would numbers

3x + 2y = 7

5x - 2y = 1

-----------------------

8x =8

x=1

Now plug x = 1 back into either equation and you can solve for y

Y = 2

When you add the 2 equations together the +2y and the -2y cancel

out

Hope this helps Loringh Please leave a rating for me Thks

You can add these equations just like you would numbers

3x + 2y = 7

5x - 2y = 1

-----------------------

8x =8

x=1

Now plug x = 1 back into either equation and you can solve for y

Y = 2

When you add the 2 equations together the +2y and the -2y cancel

out

Hope this helps Loringh Please leave a rating for me Thks

Dec 01, 2008 | Bagatrix Algebra Solved! 2005 (105101) for...

V (2,0) and Focus (2,2)

since the focus is 2 units above the vertex, the parabola opens upward

vertex (h,k)

a is the focal length (distance between the vertex and the focus)

a = 2

(2 units above the vertex)

(x-h)^2 = 4a (y-k)

(x-2)^2 = 4(2) (y-0)

x^2 - 4x + 4 = 8 (y)

x^2 - 4x + 4 = 8y

x^2 - 4x - 8y + 4 = 0

**Answer: "(x-2)^2 = 8 (y)" or in expanded form "x^2 - 4x - 8y +4"

since the focus is 2 units above the vertex, the parabola opens upward

vertex (h,k)

a is the focal length (distance between the vertex and the focus)

a = 2

(2 units above the vertex)

(x-h)^2 = 4a (y-k)

(x-2)^2 = 4(2) (y-0)

x^2 - 4x + 4 = 8 (y)

x^2 - 4x + 4 = 8y

x^2 - 4x - 8y + 4 = 0

**Answer: "(x-2)^2 = 8 (y)" or in expanded form "x^2 - 4x - 8y +4"

Nov 18, 2008 | Super Tutor Trigonometry (ESDTRIG) for PC

Just plug in one side of the equation and find the answer. Then plug in the other side and compare answers.

Feb 19, 2008 | Texas Instruments TI-89 Calculator

Nov 22, 2013 | Bagatrix Algebra Solved! 2005 (105101) for...

Nov 22, 2013 | Bagatrix Algebra Solved! 2005 (105101) for...

262 people viewed this question

Usually answered in minutes!

×